2007
DOI: 10.1002/ijc.22900
|View full text |Cite
|
Sign up to set email alerts
|

Modulating metastasis by a lymphangiogenic switch in prostate cancer

Abstract: Prostate cancer dissemination is difficult to detect in the clinic, and few treatment options exist for patients with advanced-stage disease. Our aim was to investigate the role of tumor lymphangiogenesis during metastasis. Further, we implemented a noninvasive molecular imaging technique to facilitate the assessment of the metastatic process. The metastatic potentials of several human prostate cancer xenograft models, LAPC-4, LAPC-9, PC3 and CWR22Rv-1 were compared. The cells were labeled with luciferase, a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 45 publications
(62 reference statements)
3
61
1
Order By: Relevance
“…Histology was performed, processed, and quantified as previously described. 19 The samples were analyzed using an Olympus BX41 fluorescent microscope fitted with a Q-Imaging QICAM FAST 1394 camera. Images were captured at 4ϫ, 10ϫ, or 20ϫ magnification using QCapture Pro Version 5.1 (Media Cybernetics), quantified using ImageJ Version 1.34s (NIH), and processed using Adobe Photoshop CS.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Histology was performed, processed, and quantified as previously described. 19 The samples were analyzed using an Olympus BX41 fluorescent microscope fitted with a Q-Imaging QICAM FAST 1394 camera. Images were captured at 4ϫ, 10ϫ, or 20ϫ magnification using QCapture Pro Version 5.1 (Media Cybernetics), quantified using ImageJ Version 1.34s (NIH), and processed using Adobe Photoshop CS.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…All are preclinical. Brakenhielm et al developed a new metastatic model for prostate cancer in which tumor cell lines not normally metastatic were transfected with VEGF-C, which promotes lymphangiogenesis (189). Turning on that ''lymphangiogenic switch'' could be visualized clearly with optical imaging because the cells were also transfected with fLuc as the reporter gene (Fig.…”
Section: Optical Techniques For Imaging Metastatic Potentialmentioning
confidence: 99%
“…Clinical trials on human tumors indicated that the expression of VEGF-C or VEGF-D is associated with lymph node metastasis and the poor prognosis of patients with cancer (16). using relevant animal models, it was confirmed that VEGF-C or VEGF-D plays an important role in the regulation of tumor lymphangiogenesis and lymph node metastasis in that the overexpression of VEGF-C was accompanied by intra-and/or peri-LVD and lymphatic metastasis (17). However, Karkkainen et al (18) reported that Vegfc -/-mice cannot generate lymphatic vessels via budding, leading to the dysplasia of lymphatic vessels in tissues and prenatal death from excessive fluid accumulation in tissues.…”
Section: Vegf-c and Vegf-d Vegf-c Or Vegf-d Combinesmentioning
confidence: 88%
“…Currently, the VEGF-C/VEGF-D/ VEGFR-3 signaling pathways are believed to be the most important mechanism underlying tumor lymphangiogenesis (16)(17)(18)(19)(20)(21)(22).…”
Section: Molecular Mechanism Of Tumor Lymphangiogenesismentioning
confidence: 99%